The primary types of some species of Centris bees described by European entomologists in the 18th and 20th centuries (Hymenoptera: Apidae) - Vivallo, Felipe (European Journal of Taxonomy, 2023)
In this paper are presented notes on the primary types of some species of the oil-collecting bees of the genus Centris described by the European naturalists and entomologists Amédée Louis Michel Lepeletier de Saint-Fargeau, Anders Christian Jensen-Haarup, Arthur Louis Marie Joseph Vachal, Charles Émile Blanchard, Embrik Strand, Félix Édouard Guérin-Méneville, Guillaume-Antoine Olivier, Jean Guillaume Audinet-Serville, Jean Pérez, Johann Christoph Friedrich Klug, Johann Ludwig Christ, John Obadiah Westwood, Josef Anton Maximilian Perty, Jules Dominique, Karl Hermann Konrad Burmeister, Karl Wilhelm von Dalla Torre, Massimiliano Spinola, Peter Cameron, and Wilhelm Ferdinand Erichson. Information on the type status, type locality and depository are provided. In order to stabilize some names, lectotype designations were made for Centris rhodophthalma, C. sponsa var. asuncionis, C. transversa, Hemisia byssina and Ptilotopus americanus. Centris sponsa var. asuncionis is withdrawn from the synonymy of C. sponsa, revalidated and raised to species level. Centris byssina is proposed as nomen oblitum and as a new junior synonym of C. trigonoides, nomen protectum.